INTRODUCTION TOTHE RUSSIAN MUSIC CULTURE AS A WAY OF CHINESE MUSIC TEACHERS TRAINING - N. G. Таgiltseva; Wang Bodong (Образование и наука)
Article purpose – to open the ways of introduction of the Chinese students who are trained in Chinese pedagogical higher education institutions to musical culture of Russia.Methods. The paper is based on ideas of extrapolation of the Russian and Chinese teachers about interrelation of arts and types of art activity of children in the process of vocational performing cello training of future music teachers at pedagogical universities of China; the traditional methods and means of music education that proved the efficiency in pedagogics of professional music education in Russia. The research methods involve the analysis, generalization of literature, the analysis of a condition of modern process of professional pedagogical education of future music teachers at universities of China and Russia.Results: The methods and means of introduction of the Chinese students – future music teachers to cello musical culture of Russia are shown on the basis of interrelation of arts and different means of art activities, and mastering at cello fingering techniques. It is noted that such means and ways serve mutual enrichment of national cultures, and strengthening of international relations.Scientific novelty. The most effective methods of vocational training of music teachers are revealed: polyart education that is based on comparison of different types of art (music, poetry, dance, theater, the fine arts) and search of their crossing for deeper penetration into plasticity of intonations of a piece of music; the method of a retrospective and prospect consisting in the comparative analysis of the classical, borrowed from an arsenal recognized masters and modern manners of performance and ways of training at fingering and playing the chosen musical instrument; the method of the Russian teacher, musician and composer D. B. Kabalevsky based on perception and reflection about music, expanding ideas of the range of bag, opportunities of interpretation of a piece of music, specifics of individual equipment and its esthetic features of each musician. Basic abstracts which are offered to be created by students in the course of such reflection can be used further by them in real professional activity as the main material for the musical analysis of works at school lessons.Practical significance. Recommendations on the ways realization of polyart education, method of prospect and a retrospective, perception and reflection of music and also modern tutorials of students are offered: the computer, a movie camera for vocational training of future music teachers who are trained in cello performance.